Acute Toxicity of Cadmium and Lead to Adult Toad Bufo maculatus - Enuneku, Alex Ajeh; Ezemonye, Lawrence Ikechukwu (Asian Journal of Biological and Life Sciences, 2012)
The toxicity of cadmium and lead to Bufo maculatus were assessed using acute toxicity assays in the laboratory. Mortality and behavioral changes were used as measurement end points for acute toxicity. The Organization for Economic Co-operation and Development (OECD) # 203 recommended semi static renewal bioassay with slight modification was used to determine 96hrs LC 50. Bufo maculatus was exposed to cadmium and lead concentration of 2, 4, 8, 16 and 32mg/l. Toads assumed a semi-erect posture in the highest concentration (32mg/l) lead concentration. Percentage mortality increased with increase in concentration and exposure duration. Mean percentage mortality for B. maculatus exposed cadmium and lead were significantly (p<0.05) different from control groups. Estimated LC50 concentrations were 9.97 and 16.03mg/l for cadmium and lead respectively. This indicated that B.moculatus was more sensitive to cadmium than lead. The study suggests that the release of cadmium and lead into the environment could possibly affect the well-being of amphibians and result in further decline of these sensitive organisms that contribute significantly to the food web. There is therefore the need to protect amphibians from habitat alteration due to metal pollution with a view to sustaining the rich biodiversity in the Nigerian Niger Delta ecological zone.